Jesus’ Explanation of 1Mos 2:24 and Current Tendencies of Interpretation - Vladár, Gábor (Booklets of Sárospatak, 2024)
This short lecture will explore how Genesis 2:24 (“Therefore a man leaves his father and his mother and clings to his wife, and they become one flesh.”) has received non-traditional interpretation in Genesis commentaries over the last hundred years. Jesus referred to this text as the basis for marriage (Mk 10:7, 8; Mt 19:5), as traditional theological thought has viewed it the same way. According to contemporary commentaries on Genesis, however, Genesis 2:24 is not “The Magna Carta” of the institution of marriage but a passage about the elemental attraction of man and woman to each other, which is the result of their creation. This presentation will try to reveal the background of this new exegetical perspective.
Keywords: marriage; affection; Genesis; communion; male-female